Flow of a Bingham Fluid Through Circular Pipes with Variable Viscosity Coefficient Along the Pipe Length - Zadorozhnyi, Andrii; Kovrevski, Artur; Chovnyuk, Yuriy; Remarchuk, Nikolay (International Journal of Engineering and Technology, 2018)
Creation of conditions for optimal flow of Bingham media, such as ready-mixed concrete and mortar mixes, in the circular pipeline during delivery by various types of transporting equipment has not been sufficiently studied so far. Purpose: finding patterns of flow of concrete and mortar mixes in different sections of the pipeline, based on the variability of the viscosity coefficient when the medium is flowing through long circular pipes. In calculations of the flow capacity of mortar and concrete pipelines and the required power of the pumping equipment, the properties of concrete and mortar as Bingham media should be taken into account. Dependences for description of the operation process of flow of concrete and mortar mixes through circular pipelines have been found on the basis of the Buckingham equation in the laminar flow mode.Dependences of determination of flow rate and required power with continuous delivery of concrete and mortar mixes in the pipeline, as well in case of alternate inlet pressure variation are presented. Law of variation of Î¼Ñ€ can be obtained only experimentally, which also results in errors in the computation model.Â Â